Differences in the prevalence of metabolic disorders between prepubertal boys and girls from 5 to 8 years of age. (24th January 2014) - Maier, Ina B.; Özel, Yelda; Engstler, Anna Janina; Puchinger, Sonja; Wagnerberger, Sabine; Hulpke‐Wette, Martin; Bischoff, Stephan C.; Bergheim, Ina
Abstract Aim To determine the prevalence of metabolic abnormalities, and differences between the sexes, in prepubertal overweight and normal weight children aged from 5 to 8 years, without any signs of health impairments or metabolic disturbances at the time of recruitment. Methods General health status and inflammatory markers were assessed in 100 overweight and 51 normal weight children, who were living in Germany and had undergone mandatory medical examinations. The study comprised of 81 girls and 70 boys. Results Despite being recruited as healthy, 73% of the overweight children and 16% of the normal weight children were found to suffer from one or more metabolic abnormalities, such as hypertension or insulin resistance. Girls with a body mass index (BMI) percentile of ≥80th showed an increased susceptibility to metabolic disorders, and a similar effect was found for boys with a BMI percentile of ≥95th. Plasma levels of pro‐inflammatory markers, such as plasminogen activator inhibitor‐1 and leptin, were also significantly higher in overweight than normal weight children. Conclusion Metabolic and cardiovascular abnormalities and pro‐inflammatory markers were prevalent in overweight prepubertal children. The prevalence rates appeared to differ between the sexes.